Applications Multiplatform in the Education Sector : A Literature Review - Maosul, Asep; Mustofa, Ginny Ginanjar; Muktiarni, Muktiarni; Nugraha, Hari Din (Media Pendidikan Gizi dan Kuliner, 2024)
This paper aims to discuss multiplatform applications in education. Literature review is used to examine several relevant journals published from 2015 to 2019. The method used in this research is literature review analysis which is carried out to describe multiplatform applications as learning media in the world of education. The results can be reported that multi-platform applications, which are currently a trend in the field of education, can be an effective tool to facilitate online learning and support the concept of heutagogy learning for the realization of students who have lifelong learning skills. The findings of this literature review show that the use of multiplatform applications in education can enable the learning process to be easier, more interesting, effective and efficient.